Ophthalmic Causes of Headache among Patients Attending Tertiary Care Center in Kathmandu, Nepal - Singh, Pranisha; Mishal, Anu; Sunarait, Jay Sundar (Nepal Medical College Journal, 2021)
The purpose of this study was to evaluate the ophthalmic causes of headache among patients attending tertiary care hospital. This was a descriptive, cross sectional hospital-based study. One hundred and thirty-two patients with ocular cause of headache excluding primary headache and pediatrics patients during one year were included. Detail ocular examination was done including visual acuity, refraction, binocular vision assessment like convergence insufficiency and fusional insufficiency, anterior and posterior segment examination. Among headache patients, female was 106 (80.3%) and male was 26 (19.7%). The prevalence of headache in female was 6.9% and in male was 2%. Headache was more common in age group 18-29 (59.8%). The mean age of presentation was 29.9 ± 10.2 years (range 18-61 years). Out of 132 patients with headache, 104 (78.8%) had refractive error, 15 (11.4%) had fusional insufficiency, 6 (4.5%) had convergence insufficiency, 10 (7.6%) had anterior segment diseases and 5 (3.8%) had posterior segment diseases. Among refractive errors, both eyes astigmatism was the commonest 48 (36.5%) followed by both eyes simple myopia 44 (33.4 %) which was statistically significant with ocular headache (p=0.000). Ocular anomalies other than refractive error may coexist with headache complaints. Therefore, thorough ocular examination should be done in all patients suffering from headache.